2016
DOI: 10.1590/s1413-41522016139269
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da influência das condições meteorológicas em dias com altas concentrações de material particulado na Região Metropolitana do Rio de Janeiro

Abstract: RESUMO: Na Região Metropolitana do Rio de Janeiro, altos índices de concentrações de material particulado inalável (PM10) com violações dos limites estabelecidos pela Resolução CONAMA n0 03/90 são registrados rotineiramente. Analisando dados registrados entre 1998 e 2008, foram identificados 146 dias com concentrações acima dos valores estabelecidos. Nesses dias, foi possível verificar a influência da atuação do Anticiclone Subtropical do Atlântico Sul, a ausência de precipitação e a ocorrência de inversões té… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 7 publications
2
13
0
3
Order By: Relevance
“…Invertebrates Fish The meteorological variables more related with atmospheric particulate matter spread were wind velocity and precipitation (Santos et al, 2016). Mattiuzzi and Marchioro (2012) described the wind prevalence in Vitória as Northeast (NE) with a velocity varying from 2.1-3.6 m/s; however, when there is a Cold Front (CF) or South Atlantic Convergence Zone (SACZ) events in the region of Vitória city, the direction and velocity of the winds changes increasing the velocity to 3.6-5.7 m/s and the predominant direction is to the Southeast.…”
Section: Plantsmentioning
confidence: 99%
“…Invertebrates Fish The meteorological variables more related with atmospheric particulate matter spread were wind velocity and precipitation (Santos et al, 2016). Mattiuzzi and Marchioro (2012) described the wind prevalence in Vitória as Northeast (NE) with a velocity varying from 2.1-3.6 m/s; however, when there is a Cold Front (CF) or South Atlantic Convergence Zone (SACZ) events in the region of Vitória city, the direction and velocity of the winds changes increasing the velocity to 3.6-5.7 m/s and the predominant direction is to the Southeast.…”
Section: Plantsmentioning
confidence: 99%
“…3, 4 and 5), which represent 72.7% of all cases under analysis, have high pressure atmospheric systems passing through or over the study area. Katsoulis (1996), Incecik (1996, Wai and Tanner (2005) and Santos et al (2016) also observed these characteristics in their studies. Besides, Santos et al (2016) have recently shown that, in Rio de Janeiro, episodes of high PM 10 concentration occur when the conditions are clear sky, light winds and lack of rain, under the influence of the subtropical anticyclone in the South Atlantic.…”
Section: Condições Atmosféricas Que Favorecem a Concentração De Poluementioning
confidence: 60%
“…Katsoulis (1996), Incecik (1996, Wai and Tanner (2005) and Santos et al (2016) also observed these characteristics in their studies. Besides, Santos et al (2016) have recently shown that, in Rio de Janeiro, episodes of high PM 10 concentration occur when the conditions are clear sky, light winds and lack of rain, under the influence of the subtropical anticyclone in the South Atlantic. In their study, Wai and Tanner (2005) also observed that the passage of cold fronts favors the accumulation of pollutants, in agreement with evidence found by this study in class 5 (Fig.…”
Section: Condições Atmosféricas Que Favorecem a Concentração De Poluementioning
confidence: 60%
See 1 more Smart Citation
“…O ruído característico da queima do diesel faz do motor a principal fonte de ruído em máquinas movidas a diesel (Parizet et al, 2004). Além disso, a combustão dos derivados de petróleo, como o diesel, contribui com a emissão de muitos gases poluentes (Perin et al, 2015), impactando negativamente a saúde humana e promovendo alterações climáticas (Santos et al, 2016). Uma alternativa para a redução desses poluentes pode estar relacionada à utilização de combustíveis que promovam uma combustão mais limpa e silenciosa.…”
unclassified